Context is key: A 34‐country analysis investigating how similar HRM systems emerge from similar contexts - Mayrhofer, Wolfgang; Biemann, Torsten; Koch‐Bayram, Irmela; Rapp, Marco L. (Human Resource Management, 2024)
AbstractUsing an institutional lens, we investigate the isomorphic effects of both external and internal contexts on human resource management (HRM) systems. Our analysis uses data from 4768 organizations across 34 countries to focus on the similarities in HRM systems. By employing distance matrices, a commonly adopted method in geographic science, we find that both external and internal contexts affect (dis)similarities in HRM systems. Organizations in similar environments exhibit more similar HRM systems. Furthermore, we find that the devolvement of HRM activities from HRM to line management reduces the similarity of HRM systems across organizations. By contrast, a strong strategic position of HRM does not yield a comparable effect. Our study's main contributions include elucidating the multifaceted relationship between context and HRM, highlighting the HRM department's role in this relationship, clarifying the context–HRM connection via the concept of isomorphic pressures, and illustrating the use of distance matrices as tool with great explanatory power for the analysis of similarities among HRM phenomena.